Job Satisfaction of School Teachers in Nepal: A Systematic Literature Review - Khadka, Subarna Kumar; Bhatnagar, Shivani (Journal of Nepalese Management and Research, 2025)
Teacher job satisfaction is one of the indicators as to how well they teach, how long they remain in the profession, and how the overall quality of education is affected. In Nepal, satisfaction on the job of teachers is influenced by various social, economic, institutional, and cultural factors. These are various depending on the type of school and its location. This study aims to consolidate the empirical research conducted between 2011 and 2025 to identify the principal determinants, existing patterns and educational implications of job satisfaction among school teachers in Nepal.  We conducted a systematic thematic review based on the thirty empirical studies which retrieved from Google Scholar, NepJOL, DOAJ, Elsevier, and ResearchGate. We analyzed studies that discussed a number of factors, internal and external, that determine job satisfaction of teachers, and how these factors interrelate to teachers’ self-efficacy and performance, as well as organizational commitment.  Job satisfaction among teachers in Nepal is found to be moderate, and is shaped by factors such as inner satisfaction, student engagement, professional identity, and social contribution of one’s profession. On the contrary, external factors of low salary, limited promotion, poor physical facilities, and political instability are definitive factors that shape the dissatisfaction of teachers. Professional fulfillment varies by sex, region, and kind of school. There is substantial research connecting satisfaction to successful teaching, classroom efficacy, dedication to an organization, and harmony of the personal and professional realms. Improving job satisfaction among teachers in Nepal will require significant overhauls to remuneration systems, professional advancement opportunities, administrative approaches, and the overall school climate. At a national scale, to enhance the quality and equitable sustainability of education, the institutional support for teachers requires broad improvements.